The Michelin rating system: Cracking the code of the stars - CHEE, Jonathan (Institutional Knowledge at Singapore Management University, 2021)
Since the young age of 15, Andre Giraud, the owner-chef of Lux, a 1 Michelin-star French restaurant located in Hong Kong, had devoted his life to cooking. After 17 years of working for top chefs in Europe, he decided that it was time to bring his talent to Asia. Andre and his wife decided to invest their life savings to open Lux, a 35-seater at the heart of Hong Kong’s central business district. Having never been involved in the business side of running a restaurant, Andre needed his business partner Brandon to evaluate and manage the restaurant’s finance, marketing and operations. In 2017, Lux was awarded 2 Michelin stars. However, the following year, it suffered a demotion, resulting in a massive drop in restaurant reservations that left him with only three months of runway. Andre contemplated closing the doors to his restaurant, as he had no idea about what needed to be improved. However, the local food guides and his social media feeds seemed to indicate he was doing great things in the kitchen. He suffered from depression as a result of the unexplainable loss of the Michelin star, and decided to reach out to Pierre E., a long-time friend and a former Michelin inspector, to find out more about the criteria the guide adopts in reviewing an establishment. In this case study, students are taught to perform business evaluations with informational asymmetry, incomplete data, and limited resources. They are invited to discuss how information asymmetry is sometimes caused by agency issues; explore innovative ways to source for data; and create a framework when under a limited time frame, to evaluate external and internal variables for scoring a firm’s success.